The social and human rights models of disability: towards a complementarity thesis. Issue 2 (7th February 2021) - Lawson, Anna; Beckett, Angharad E.
ABSTRACT: This article aims to reorient thinking about the relationship between the long-standing social model of disability and the rapidly emerging human rights model. In particular, it contests the influential view that the latter develops and improves upon the former (the improvement thesis) and argues instead that the two models are complementary (the complementarity thesis). The article begins with a discursive analysis of relevant documents to investigate how each of the two models has been used in the crafting and monitoring of the UN Convention on the Rights of Persons with Disabilities. This highlights the increasing importance of the human rights model in this policy context. It also provides examples of the operation of the two models which inform the remainder of the discussion. We then critique the comparisons between the models which underpin the improvement thesis; and, drawing on Foucault's technologies of power and Beckett and Campbell's 'oppositional device' methodology, deepen and develop this comparative analysis. The result, we argue, is that the two models have different subjects and different functions. In the human rights context, their roles are complementary and supportive.